The Effectiveness of Group Cognitive Behavioral Therapy on Depression and Sense of Security in Women with Marital Distress - Teimuri , Mehrnaz; Maleki , Elnaz; Imani Movahed , Maryam; Islami , Alireza; Afzali , Maryam (Psychology of Woman Journal, 2023)
Objective: The aim of this research was to determine the effectiveness of group cognitive behavioral therapy (CBT) on depression and sense of security in women experiencing marital distress. Methods and Materials: The research method was quasi-experimental, employing a pre-test and post-test design with a control group. The statistical population of this study included women with marital distress who referred to counseling centers in Tehran in 2022. The sampling method was purposive, and using this method, 28 individuals were selected as the sample and randomly assigned to two groups: experimental (14 individuals) and control (14 individuals). Data were collected using questionnaires on depression and sense of security. Group CBT was conducted in eight 120-minute sessions for the experimental group. After the completion of the group CBT sessions, post-tests were administered to both the experimental and control groups. Findings: The findings indicated that the mean scores of depression and sense of security in the post-test of the experimental group were significantly different from the pre-test. Conclusion: Therefore, group cognitive behavioral therapy affects depression and sense of security in women with marital distress.